Upaya Meningkatkan Minat dan Hasil Belajar Sosiologi Dengan Pendekatan Kontekstual (CTL) Siswa Kelas X6 SMA NEGERI 4 MADIUN Tahun Ajaran 2025/2026 - Dewi Susiawati; Ibadullah Malawi; Sudarmiani (Mataram University, 2025)
Students’ relatively low learning interest, along with the conditions of both students and teachers, has influenced learning outcomes in sociology. This study examines the use of the Contextual Teaching and Learning (CTL) approach to enhance students’ interest and learning outcomes in sociology, with the theme of applying basic sociological concepts to understand various social phenomena in society among Grade X-6 students of SMA Negeri 4 Madiun in the 2025/2026 academic year. Based on the research findings, the average level of students’ learning interest at the end of learning in Cycle I was 69, while in Cycle II it increased to 81.66, indicating a clear improvement in students’ learning interest. Furthermore, a comparative analysis of sociology learning outcome data reveals a highly significant improvement in students’ academic achievement. In Cycle I, only 6 students (17%) achieved the mastery criteria, with a class average score of 69, whereas the majority of students (29 students or 83%) still required remedial instruction. However, following the implementation of the contextual learning approach in Cycle II, a remarkable transformation occurred: all students (35 students or 100%) successfully achieved learning mastery, and the class average score rose substantially to 81.66. Therefore, it can be concluded that the contextual learning approach is effective in improving both learning interest and sociology learning outcomes of Grade X-6 students at SMA Negeri 4 Madiun in the 2025/2026 academic year.